The Crime of Water Assaulting - ALKHSEILAT, Abdullah; ALMANASRA, Majd; ALKHAWAJA, Noor (Journal of Environmental Management and Tourism; Vol 13 No 3 (2022): JEMT, Volume XIII, Issue 3(59), Summer 2022DO - 10.14505/jemt.v13.3(59).21, 2022)
The world's governments seek to ensure that water needs of their citizens are met and that water security is provided; water resources are preserved and used rationally as an important source of economic development. It also criminalizes all types of assaulting against water and imposes deterrent penalties on every trespasser on water resources. Therefore, legislators in these countries have criminalized assaults on all sources of water and imposed penalties. This is done by our Jordanian legislator, whether in the Water Authority Act No. 18/1988 and its amendments to Act No. 17 of 2014 or through the provisions of the Jordanian Penal Code.